Spanish monarchy and the Portuguese Republic: two routes to democratization - Roda, Federico Martinéz (2016)
From 1974 to 1986 the Iberian Peninsula was the arena of major political changes. The process then undertaken was characterized by the transition from two Iberian authoritarian regimes to two democracies, which enabled both countries to join the European Economic Community (EEC) on 1 January 1986. However, the political vicissitudes until full membership of what became the European Union (EU) was achieved were very different and were decisively, although not exclusively, influenced by the fact Portugal was a republic and Spain a monarchy. In Portugal the 1974 revolution took place with consequent shift of the head of state while in Spain the engine of change was precisely the head of state: King Juan Carlos I. It is also true that despite the dangers to democracy (terrorism in Spain and some radicalism in Portugal) both societies supported the political parties committed to the democratic process in elections, which helped avoid tensions that could have defeated the process. Likewise, it is possible to argue that in Spain a plan to achieve democracy within the rule of law (an archetypal transition) was designed by the head of state, while in Portugal there was no pre-established plan – the programme of the Armed Forces Movement (Movimento das Forças Armadas [MFA]) was a weak and precarious compromise between different visions of the road to follow, enabling an intense political struggle that almost led to civil war and a dangerous state of crisis.